Expanding the understanding: transactions and security awareness for ebusiness students - Petrova, K.; Sinclair, R. (NACCQ, 2003)
The lack of popularity in buying goods and services online can be traced to a concern for the lack of security of the system. Therefore, it is crucial that students studying an undergraduate business degree majoring in eBusiness have an understanding of the security risks that businesses may face. To expand the understanding of security students must comprehend the nature of a transaction in order to holistically access the security needs of an eBusiness. This also leads to a need to understand transactions both from business and information technology points of view. Most businesses look at transactions from a financial viewpoint rather than a broad interpretation of the word 'transactions'. This paper discusses the content, teaching methods and assessment in a module called "Electronic Transactions and Security". It also highlights the importance of a multi-discipline teaching partnership between two distinct academic groups to further develop students' understanding of electronic transactions, risk management and security awareness.
Keywords: eBusiness; Electronic; Transactions; Security awareness